2019
DOI: 10.20945/2359-3997000000098
|View full text |Cite
|
Sign up to set email alerts
|

Does the Bethesda category predict aggressive features in differentiated thyroid cancer?

Abstract: Objective: To analyze the importance of preoperative cytology of thyroid nodules and its relationship with mortality risk, recurrence risk, dynamic stratification, and aggressive characteristics (vascular invasion, aggressive histology, incomplete tumor resection, extrathyroidal extension of the tumor, and presence of lymph node and distant metastases). Subjects and methods: Retrospective evaluation of 153 patients diagnosed with differentiated thyroid carcinoma (DTC) and following up at the Hospital Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
2
5
0
Order By: Relevance
“…Our study did not reveal an association between cytological diagnosis and recurrence risk, corroborating results from other authors (12). However, a recent large study reported an association between both (10), guiding their conclusions towards a relationship between cytology and findings that could suggest a higher risk of recurrences, such as histological subtype and the presence of local recurrence and distant metastases.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Our study did not reveal an association between cytological diagnosis and recurrence risk, corroborating results from other authors (12). However, a recent large study reported an association between both (10), guiding their conclusions towards a relationship between cytology and findings that could suggest a higher risk of recurrences, such as histological subtype and the presence of local recurrence and distant metastases.…”
Section: Resultssupporting
confidence: 91%
“…In this study, the 7 th edition of AJCC/TNM (19) was considered, once that it was the parameter in force at the time of data collection. No association was seen between cytological diagnosis and risk of death, similar to descriptions by other authors (12,14), but different to the findings of VanderLaan and cols., who found an association between Bethesda cytology Class VI and the more advanced TNM stages (8). AJCC/TNM staging was also not associated to disease status in final evaluation, reinforcing the concept that it does not have prognostic value regarding therapeutic response or disease persistence, restricting itself as just a predictor of mortality from neoplasia (29).…”
Section: Thyroid Cancer: Cytology Versus Prognosissupporting
confidence: 63%
See 2 more Smart Citations
“…The preoperative diagnosis of Bethesda II was observed in a higher than expected number of patients with DTC (29.4%). Fortunately, the vast majority of DTC patients that presented with Bethesda II evolved with excellent response to therapy and no evidence of disease (92.1%) (6). According to the Bethesda system the implied risk of malignancy for the diagnostic category II (benign) is of 0-3% and the recommended clinical approach is clinical and sonographic followup (7).…”
mentioning
confidence: 99%